Investigation of geopolymers containing fly ash and ground-granulated blast-furnace slag blended by amorphous ratios. (20th October 2019) - Lau, Chee Keong; Rowles, Matthew R.; Parnham, Glenn N.; Htut, Trevor; Ng, Tian Sing
Highlights: Amorphous based mix design framework had been developed for blended geopolymers. The varying composition of slag and fly ash in blended geopolymer is investigated. The optimal amorphous Si/Al ratio of blended geopolymer is 2.3. New amorphous ratio, (Na + 2Ca)/Al, is proposed with optimal ratio 3.2. Abstract: A new amorphous phase mix design framework had been successfully developed in consideration of calcium content through the combination of ground-granular blast-furnace slag (GGBFS) in fly ash (FA) blended geopolymers. The new framework has been developed considering the amorphous silicon, aluminium, sodium and calcium containing phases of the aluminosilicate sources to increase geopolymerisation reactivity and compressive strength. By utilising this new framework, this study found that the optimal amorphous Si/Al ratio of FA- and GGBFS-blended geopolymers are between 2.3 and 3.1. At 40–50% of FA replacement with GGBFS, it had been observed that blended geopolymers are able to achieve the majority of its 28 days compressive strength at 7 days. To account for the effect of calcium content, a new amorphous ratio, (Na + 2Ca)/Al, is proposed, with an optimal ratio of between 3.2 and 3.4.